Fatty acids profiles and growth performances of Artemia franciscana fed with different types of microalgae - Amin, Muhamad; Erwinda, Mugi; Maschlahatun Nissa,; Nindarwi, Daruti D; Woro H Setyantini,; Mubarak, Ahmad S; Patmawati,; Dwi Y Pujiastuti,; Sulmartiwi, Laksmi; Andriyono, Sapto; Alamsjah, Mochammad Amin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Artemia has been considered as one of the most important live diets for crustacean and finfish larviculture as well as broodstocks. However, the basal nutrient of Artemia has been reported to be poor in polyunsaturated fatty acids (PUFA’s) especially eicosapentaenoic acids (EPA) and docosahexaenoic acids (DHA), essential fatty acids for larval normal growth and gonad maturity in shrimp broodstocks. Thus, the present study aimed at investigating the effect of different microalgal diets on fatty acid content, growth performances and survival rate of Artemia francisciana. The study was performed by culturing instar I nauplii of A. franciscana for 12 days at a stocking density of 100 nauplii/L and fed with one of these microalgae: Chaetoceros calcitrans (T1), Dunaliella salina (T2), Tetraselmis chuii (T3), and Nanochloropsis oculata (T4). The results showed that the different microalgal diets affected fatty acid content, growth and survival rate of A. fransicana. The highest DHA content was obtained from those Artemia fed on D. salina, p<0.05. While DHA content of A. fransciscana fed with the other three microalgae was not significantly different, p>0.05. Another result indicated that EPA contents in the Artemia biomass were not significantly affected by the microalgal diets, p>0.05. In terms of growth and survival rate, A. franciscana fed on C. calcitrans and T. chuii had better growth and survival rate compared to that of Artemia fed on either D. salina or N. oculata, p<0.05. Due to the faster growth, it was also observed that Artemia fed on T. chuii started producing eggs on day 12. Further studies by feeding the Artemia with a mix of microalgal species either a mix of T. chuii and D. salina or a mix of C. calcitrans and D. salina are highly recommended for better PUFA contents, specific growth rate (SGR) as well as survival rates of Artemia.